2016
DOI: 10.1103/physrevb.94.014106
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing anisotropic propagation of stripe domain walls in staircaselike transitions ofIrTe2

Abstract: We present a scanning tunneling microscopy (STM) study of the domain evolution across two first-order phase transitions of stripe modulations in IrTe 2 that occur at T C ≈ 275 K and T S ≈ 180 K, respectively. Phase coexistence of the hexagonal (1 × 1) structure and the (5 × 1) stripe modulation is observed at T C , while various (p × 1) modulations (p = 3n + 2 with 2 ≤ n ∈ N) are observed below T S . Using STM atomic resolution, we observe anisotropic propagation of domain boundaries along different directions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 43 publications
(32 reference statements)
6
21
0
Order By: Relevance
“…Therefore, phases of different stripe periodicities appear with increasing dimer densities as temperature decreases. Their complex kinetics, involving dimers breaking and reassembling, has been studied by Mauerer et al [12]. Interestingly, a very recent study predicts the correct T c 1 by considering the entropy of the (5 × 1 × 5) phase [33].…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…Therefore, phases of different stripe periodicities appear with increasing dimer densities as temperature decreases. Their complex kinetics, involving dimers breaking and reassembling, has been studied by Mauerer et al [12]. Interestingly, a very recent study predicts the correct T c 1 by considering the entropy of the (5 × 1 × 5) phase [33].…”
Section: Introductionmentioning
confidence: 95%
“…At T c 2 ∼ 180 K, a second phase transition follows and the charge-ordering wave vector of this new low-temperature phase is (8 × 1 × 8) in the bulk of IrTe 2 . This has stimulated many scanning tunneling microscopy (STM) studies, which evidenced additional ordering patterns and revealed a surface (6 × 1) periodicity proposed to be the ground-state reconstruction [12,16,25,28]. In addition, a detailed low-energy electron diffraction (LEED) and STM study observed the coexistence of the surface (8 × 1) and (6 × 1) phases over a wide temperature range [29].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, with the bulk 5×1×5 phase, all that can be seen is a 5×1 surface phase. The surface properties of IrTe 2 have been investigated using STM, which probes the local charge density but can infer the structural symmetry [17,18,[31][32][33]. In contrast to the bulk, the fully dimerized 6×1 modulation [ Fig.…”
Section: Introductionmentioning
confidence: 99%